The Effectiveness of Mobile-Based E-Assessment and Educational Supervision on the Performance of Upper-Class Elementary School Teachers, Susukan District, Cirebon Regency (Educational Management, 2022)
The research purpose to analyze educator anxiety about the challenges of changing times. The era of the industrial revolution 4.0 brought together automation technology with cyber technology, directing educators to change the paradigm of life by developing new ways of working based on IoF (Internet of Things) in carrying out their duties at school. The teacher's problems or difficulties in implementing the research-based curriculum are low competence, work ethic, work motivation, lack of technology skills, principal leadership, and supervision techniques. This study uses a quantitative design with a One-Group Posttest-Only Design. The study population was 94 upper class elementary school teachers, Susukan sub-district, Cirebon district. Samples were taken using the technique simple random sampling. The results showed that: (1) mobile-based e-assessment partially had a significant effect on teacher performance with a sig. 0.000 < 0.05; (2) educational supervision partially has a significant effect on teacher performance with gradessig. 0.000 < 0.05; (3) mobile-based e-assessment and educational supervision simultaneously have a significant effect on teacher performance Based on the results of the study, it can be concluded thate-assessmentmobile-based and educational supervision partially and simultaneously have a positive and significant effect or mobile-based e-assessment and educational supervision can improve teacher performance.